2022
DOI: 10.7759/cureus.23777
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma Significantly Reduces Bacteriophage Infectivity Against Staphylococcus aureus Clinical Isolates

Abstract: Bacteriophage therapy has been regaining interest as a potential therapeutic in treating a wide range of infections. However, there is a paucity of knowledge regarding numerous aspects of bacteriophage therapy, thereby hindering the development of proper treatment protocols and effective clinical trials. In this report, the activities of three bacteriophages are evaluated against clinical bacterial isolates in the presence and absence of human plasma (HP). The bacteriophages used in this experiment were residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
(26 reference statements)
4
16
0
Order By: Relevance
“…When bacteria interact with polymers, the wall teichoic acid receptor is masked or obscured thereby hindering bacteriophages from attaching to this binding receptor. In human plasma this has also been previously reported 23,24 . These findings are important for clinicians to be cognizant about because if a bacteriophage cannot bind to a surface receptor no lysis will occur.…”
Section: Discussionsupporting
confidence: 74%
“…When bacteria interact with polymers, the wall teichoic acid receptor is masked or obscured thereby hindering bacteriophages from attaching to this binding receptor. In human plasma this has also been previously reported 23,24 . These findings are important for clinicians to be cognizant about because if a bacteriophage cannot bind to a surface receptor no lysis will occur.…”
Section: Discussionsupporting
confidence: 74%
“…More accurate results regarding phage susceptibility could potentially be achieved by resembling physiological conditions during bacterial infection, including phage susceptibility testing in the presence of human serum. However, the OD assay is not suitable to test phage susceptibility in this way, as serum components (such as fibrinogen and immune globulins) cause S. aureus to clump together in aggregates [ 65 ]. Microcalorimetry (MC) measures the metabolic activity of bacteria instead of optical density and is therefore not affected by S. aureus aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, these results confirm previous observations by Shinde et al (2022), who showed reduced phage infectivity under similar conditions. However, in the study of Shinde et al, bacterial aggregation was observed to be a limitation of the test [ 65 ]. The lack of phage susceptibility in serum could, in part, be due to a reduced growth rate of S. aureus in human serum, resulting in reduced phage propagation [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shinde et al. examined the effect of 10% human plasma on the lytic efficacy of two phages (Staphylococcal phage 1 and 3) against multiple S. aureus isolates in vitro [ 42 ]. It was found out that human plasma diminished the phages' infectivity substantially.…”
Section: Resultsmentioning
confidence: 99%